The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Gossypiboma-derived lethal sarcoma in a dog - A. Rigillo; G. Giulia; M. Gambini; R. Magnoni; C. Perri; S. Remoli (Journal of Comparative Pathology, 2025)

A case of feline intraocular neoplasm with neural crest derivation - M. Gambini; S. Bo; A. Rigillo; C. Perri; W. Marchioro; C. Giudice (Journal of Comparative Pathology, 2025)

The role of nutrition background on motivations, barriers, and adherence to a vegan diet: A qualitative study of the vegan eating habits and nutritional evaluation survey (VEGAN-EatS) - Martin Hindermann Santini; Heloísa C. Santo André; Bruna Caruso Mazzolani; Fabiana Infante Smaira; Gabriel Perri Esteves; Alice Erwig Leitão; Bruno Gualano; Hamilton Roschel (Food Quality and Preference, 2025)

ELIME-IMS hybrid assay for Salmonella detection in swine mesenteric lymph nodes at slaughterhouse - M. Trevisani; M. Conter; M. Cecchini; L. Lamperti; L. Andriani; M. Rega; C. Bacci; M. Perri; S. Bonardi (Food Microbiology, 2025)

Assessing potentially toxic elements (PTEs) content in asbestos and related groundwater: A review of the levels detected - A. Bloise; I. Fuoco; G. Vespasiano; F. Parisi; M.F. La Russa; C. Piersante; G. Perri; S. Filicetti; A. Pacella; R. De Rosa; C. Apollaro (Science of The Total Environment, 2024)

CME propagation through the heliosphere: Status and future of observations and model development - Manuela Temmer; Camilla Scolini; Ian G. Richardson; Stephan G. Heinemann; Evangelos Paouris; Angelos Vourlidas; Mario M. Bisi; N. Al-Haddad; T. Amerstorfer; L. Barnard; D. Burešová; S.J. Hofmeister; et al. (Advances in Space Research, 2023)

Correlations between cerebrospinal fluid biomarkers, neurocognitive tests, and resting-state electroencephalography (rsEEG) in patients with HIV-associated neurocognitive disorders - A. Barco; S. Orlando; G. Stroffolini; V. Pirriatore; A. Lazzaro; D. Vai; G. Guastamacchia; G. Noce; C. Atzori; M. Trunfio; S. Bonora; G. Di Perri; et al. (Journal of NeuroVirology, 2022)

Ancient DNA suggests modern wolves trace their origin to a Late Pleistocene expansion from Beringia - Liisa Loog; Olaf Thalmann; Mikkel‐Holger S. Sinding; Verena J. Schuenemann; Angela Perri; Mietje Germonpré; Herve Bocherens; Kelsey E. Witt; Jose A. Samaniego Castruita; Marcela S. Velasco; Inge K. C. Lundstrøm; Nathan Wales; et al. (Molecular Ecology, 2020)
Grey wolves ( Canis lupus ) are one of the few large terrestrial carnivores that have maintained a wide geographical distribution across the Northern Hemisphere throughout the Pleistocene and Holocene. Recent genetic studies have suggested that, despite this continuous presence, major demographic changes occurred in wolf populations between the Late Pleistocene and early Holocene, and that extant wolves trace their ancestry to a single Late Pleistocene population. Both the geographical origin of this ancestral population and how it became widespread remain unknown. Here, we used a spatially and temporally explicit modelling framework to analyse a data set of 90 modern and 45 ancient mitochondrial wolf genomes from across the Northern Hemisphere, spanning the last 50,000 years. Our results suggest that contemporary wolf populations trace their ancestry to an expansion from Beringia at the end of the Last Glacial Maximum, and that this process was most likely driven by Late Pleistocene ecological fluctuations that occurred across the Northern Hemisphere. This study provides direct ancient genetic evidence that long‐range migration has played an important role in the population history of a large carnivore, and provides insight into how wolves survived the wave of megafaunal extinctions at the end of the last glaciation. Moreover, because Late Pleistocene grey wolves were the likely source from which all modern dogs trace their origins, the demographic history described in this study has fundamental implications for understanding the geographical origin of the dog.

Blood Brain Barrier Impairment in HIV-Positive Naïve and Effectively Treated Patients: Immune Activation Versus Astrocytosis - A. Calcagno; A. Romito; C. Atzori; V. Ghisetti; C. Cardellino; S. Audagnotto; E. Scarvaglieri; F. Lipani; D. Imperiale; G. Di Perri; S. Bonora (Journal of Neuroimmune Pharmacology, 2017)

Blood brain barrier impairment is associated with cerebrospinal fluid markers of neuronal damage in HIV-positive patients - A. Calcagno; C. Atzori; A. Romito; D. Vai; S. Audagnotto; M. L. Stella; C. Montrucchio; D. Imperiale; G. Di Perri; S. Bonora (Journal of NeuroVirology, 2016)

Prevalence and predictors of blood-brain barrier damage in the HAART era - A. Calcagno; M. C. Alberione; A. Romito; D. Imperiale; V. Ghisetti; S. Audagnotto; F. Lipani; S. Raviolo; G. Di Perri; S. Bonora (Journal of NeuroVirology, 2014)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Isolation, Identification, Synthesis, and Field Evaluation of the Sex Pheromone of the Brazilian Population of Spodoptera frugiperda - Luciane G. Batista-Pereira; Kathrin Stein; André F. de Paula; Jardel A. Moreira; Ivan Cruz; Maria de Lourdes C. Figueiredo; José Perri; Arlene G. Corrêa (Journal of Chemical Ecology, 2006)